2016
DOI: 10.1007/s40596-016-0543-x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Psychiatry’s Role in Addressing Campus Sexual Assault

Abstract: In 2011, the US President, Vice President, and Secretary of Education spotlighted the serious and pervasive issue of sexual assault in institutions of higher learning, offering comprehensive guidance to colleges and universities regarding student rights and needs. In 2014, the White House Task Force to Protect Students from Sexual Assault was established and the "It's On Us" public health campaign was launched, aiming to inspire and engage all members of college campus communities in preventing sexual assault … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…36,[72][73][74] This is likely related to unique power differentials, 24 which may be driven by prejudicial views toward the discipline of psychiatry that disproportionately sensitize trainees to IHD. 75 Factors related to compassion fatigue and burnout may also be more common among psychiatry trainees given the empathic demands of their work and vicarious exposure to IHD. 69 Psychiatrists are also paid the least among medical specialties-a systematic factor that is outside of the immediate control of most physicians.…”
Section: Ihd Among Psychiatry Residentsmentioning
confidence: 99%
“…36,[72][73][74] This is likely related to unique power differentials, 24 which may be driven by prejudicial views toward the discipline of psychiatry that disproportionately sensitize trainees to IHD. 75 Factors related to compassion fatigue and burnout may also be more common among psychiatry trainees given the empathic demands of their work and vicarious exposure to IHD. 69 Psychiatrists are also paid the least among medical specialties-a systematic factor that is outside of the immediate control of most physicians.…”
Section: Ihd Among Psychiatry Residentsmentioning
confidence: 99%
“…Jozkowski and Ekbia (2015) suggest developing several sexual assault prevention programs that can be used together, such as the video game program during the first year of studies, while promoting more direct intervention in cases of assault later on. Roberts et al (2016) suggest greater student inclusion in sexual assault prevention programs and more attention given to students of all gender identities. Finally, one could examine whether the addition of an online tutorial in safe sex practices and consent would help to decrease the rate of sexual assault in first-year students.…”
Section: Prevention Programsmentioning
confidence: 99%
“…However, despite the widespread prevalence of sexual violence on university campuses, few individuals actually report their victimization through official channels (Karjane et al , 2005), and the figures found in surveys do not correspond to those in official reports. One seminal study found that only 5 percent of assaults are reported to law enforcement (Koss, 1988), while another found that less than 5 percent of sexual assault, harassment, or stalking incidents were reported to university officials (Roberts et al , 2016). By contrast, students who have experienced sexual assault do disclose to family members or friends (Roberts et al , 2016) and to surveys.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations